Are Higher Operator Volumes for Unprotected Left Main Stem Percutaneous Coronary Intervention Associated With Improved Patient Outcomes?: A Survival Analysis of 6724 Procedures From the British Cardiovascular Intervention Society National Database. (June 2020) - Kinnaird, Tim; Gallagher, Sean; Anderson, Richard; Sharp, Andrew; Farooq, Vasim; Ludman, Peter; Copt, Samuel; Curzen, Nick; Banning, Adrian; Mamas, Mamas
Abstract : Background: The relationship between operator volume and survival after unprotected left main stem percutaneous coronary intervention (uLMS-PCI) is poorly defined. Methods: Data from the British Cardiovascular Intervention Society national PCI database were analyzed for all uLMS-PCI procedures performed in England and Wales between 2012 and 2014 and 4 quartiles of annualized uLMS-PCI volume (Q1–Q4) generated. Individual logistic regressions were performed for 12-month mortality to quantify the independent association between operator quartile and outcomes. Results: In total, 6724 uLMS-PCI procedures were analyzed with a negatively skewed distribution and an annualized median of 3 procedures per year. Operator volume ranged from 1 to 54 uLMS-PCI procedures/year. Within Q1, 347 operators performed a median of 2 procedures/year (interquartile range, 1–3); in Q2, 134 operators performed a median of 5 procedures/year (interquartile range, 4–6); in Q3, 59 operators performed a mean of 10 procedures/year (interquartile range, 8–12); and in Q4, 29 operators performed a mean of 21 procedures/year (interquartile range, 17–29). Higher volume operators undertook uLMS-PCI in patients with greater comorbid burden and performed more complex procedures compared with lower operator volumes. Adjusted in-hospital survival (odds ratio, 0.39 [95% CI, 0.24–0.67]; P <0.001), in-hospital major adverse cardiac and cerebral events (odds ratio, 0.41 [95% CI, 0.27–0.62]; P <0.001), and 12-month survival (odds ratio, 0.54 [95% CI, 0.39–0.73]; P <0.001) were lower in Q4 operators compared with Q1 operators. A close association between operator volume/case and superior 12-month survival was observed ( P <0.001). The lower volume threshold of minimum operator uLMS-PCI volume associated with improved survival was ≥16 cases/year. Conclusions: These data suggest that operator volume is an important factor in determining outcome after uLMS-PCI. Abstract : Supplemental Digital Content is available in the text.